A review of recent developments concerning the structure, mechanics and fluid flow properties of fault zones - Faulkner,DR; Jackson,C; Lunn,RJ; Schlische,RW; Shipton,ZK; Wibberley,CAJ; Withjack,MO (Journal of Structural Geology, 2010)
Fault zones and fault systems have a key role in the development of the Earth’s crust. They control the mechanics and fluid flow properties of the crust, and the architecture of sedimentary deposits in basins. We review key advances in the study of the structure, mechanics and fluid flow properties of fault zones and fault systems. We emphasize that these three aspects of faults are intimately related and cannot be considered in isolation. For brevity, the review is concentrates on advances made primarily in the past 10 years, and also to fault zones in the brittle continental crust. Finally the paper outlines some key areas for future research in this field.